Pengaruh Lingkungan Kerja Fisik Dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan Bagian Produksi PT. XYZ Di Kota Bandung - Annisa Rizki Nurhidayanti; Juddy Prabowo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In a company, one of the most important things is human resource management. PT XYZ is a company located in the city of Bandung and is engaged in textiles and textile products. Job satisfaction of production employees at PT XYZ in Bandung City is still not good, which is indicated by increased unexplained absence data. There are also factors that can affect employee job satisfaction, namely the physical work environment and work motivation. The purpose of this research was to determine the effect of physical work environment and work motivation on job satisfaction of production employees of PT XYZ in Bandung City. This research applies a quantitative-based research approach. Respondents of this study were 40 production employees at PT XYZ in Bandung City. The data collection methods used are questionnaires. The measuring scale in this study uses semantic differential. Data processing techniques using descriptive and associative analysis. The method used is multiple linear regression analysis and determination with the help of the SPSS version 26.0 program. The results showed that the physical work environment has a positive influence on job satisfaction of production employees, as well as work motivation. In addition, the physical work environment and work motivation simultaneously have an influence on job satisfaction of production employees of PT. XYZ in Bandung City. Keywords: Physical Work Environment, Work Motivation, Job Satisfaction